Reclamation of disturbed lands affected by periwinkle mining - Butenko, E.; Khomych, A.; Prokhorenko, V. (Land Management, Cadastre and Land Monitoring, 2021)
General data about processes of creation and formation of stocks of amber in the territory of Ukraine are presented. Background for the problem of illegal amber mining was specified. Illegal amber mining using motor pumps led to destruction of the soil and also to sharp deterioration of water-physical properties. it is also accompanied by the loss of many available biophilic elements and water-soluble organic compounds, in addition loosing a main substrate for soil microorganisms. There was analysed a traditional methods of soil reclamation and after that it was noticed that those methods is inefficient and, for the most, impossible to make it. The Urgent need to adopt the law of Ukraine "On land reclamation" was argued. I emphasize the need of gradual differentiation of legal terms, such as land plot «ground», «land plot » and also «soil». It was given an important attention of land reclamation. The main methods of land reclamation that have been negatively affected by amber mining have been studied.I proved that the choice of the direction of use of ex-used deposits should be based primarily on the ecological and economic feasibility of reclamation.Key words: reclamation of damaged lands ways of reclamation, damaged lands, natural condition of landscape.